An Efficient Approach for the Deprotection of Esters Using Ionic Liquid as Nucleophile - Wei, Benmei; Zhang, Zhiyong; Dai, Zhiqun; Guan, Jintao (Asian Journal of Chemistry, 2013)
An efficient approach for the deprotection of esters has been developed using ionic liquid as nucleophile in the presence of protic acid. Using methyl benzoate as a model compound, the best result was obtained by the combination of 1-methylimidazolium bromide and methane sulfonic acid with a conversion of 96 % after 2 h at 120 ºC.